Kathleen Kenyon 1906-1978 (The Biblical archaeology review, 1978)
Generally recognized as the world’s greatest field archaeologist and clearly Great Britain’s leading Biblical archaeologist, Dame Kathleen Mary Kenyon is dead at 72. Dame Kathleen died in August, less than a week after suffering a stroke. She was stricken at her home in Wrexham, North Wales.